Eksplorasi Bakteri Selulolitik dari Sampah Organik Kota Denpasar - PUSPAWATI, NI MADE INDRA; ATMAJA, I WAYAN DANA; SUTARI, NI WAYAN SRI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.7, No.3, Juli 2018, 2018)
Exploration of Cellulolytic Bacteria from Organic Waste in Denpasar Municipal waste is one of the problem that must be overcome in Denpasar City. Municipal waste volume of Denpasar City 2014 was 1,247,769 m3, Year 2015 was 1,294,696 m3, and 2016 was increased to 1,296,438 m3. Total of waste that produced by Denpasar City is 70% organic waste. This type of organic waste has a major component of lignocellulose consisting of three polymers namely, cellulose, hemicellulose, and lignin. Cellulose is a component of plant cell walls. Cellulose has a low digestibility so it takes a long time to be degraded. One of the microorganisms that can produce the enzyme is the cellulolytic bacteria. The purpose of this research was to find and identify isolate of cellulolytic bacteria isolated from organic waste of Denpasar City. This research was conducted from September to 2017 until March 2018. Organic municipal waste samples were taken from each District in Denpasar City each one sample. Bacteria from the organic waste was isolated dan identified by moleculer identification in order to know the cellulolytic bacteria spesies. Based on the result of the research, two isolates of bacteria with the highest cellulolytic indeks were B-6 and U-6 isolates that were 7.3 and 3,0. The formation of clear zones around the colony showed that the isolates had qualitatively measured cellulolytic activity. The identification of both isolates was found were the B-6 isolate had the same percentage as Lactobacillus acidophilus (95%) and U-6 isolate had similarity percentage with Enterobacter cloacae (94%).